MENINGKATKAN MOTIVASI BELAJAR DENGAN MODEL PEMBELAJARAN KETERAMPILAN MOTORIK DI KAMPUNG SANTRI CICERI JAYA - Nugraha, Enung; Hamidah, Euis; Radela, Nanda Siti; Khopipah, Pipit; Sofiyatin, Sofiyatin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
The education quality marks the value of universal education without limits. The pandemic of Covid-19 is reality to led the world of education to limit and adapt it to online learning models as expensing of low student motivation monotonous learning techniques from teachers. The research purpose to drawing of efforts to increasing students learning motivation with motor skills learning model. The research method uses a qualitative with partipatory action research approach to help overcome problems and fulfill the community's practical needs, with initial mapping stages, participatory action, and output reflection. The results showed that a program strategy stimulated students' learning motivation in the form of a motor skills learning model accompanied by offline games and crafts so that direct interaction with friends and teachers had an emotional impact on interest in learning. The implication is to increase student learning motivation through the offline motor skills learning model with health protocols' principles.